WILDFIRE RISK ZONE MAPPING FROM GEOGRAPHIC INFORMATION SYSTEM IN TAM DAO NATIONAL PARK OF VIETNAM - Duc Dat, Pham; Thai Son, Le (Journal of Forestry Science and Technology, 2022)
Tam Dao National Park is located in the north of Vietnam where many wildfires happened during the period from 2013 to 2017. This study applied GIS in forest fire risk mapping in Tam Dao National Park that supports forest fire early detection and prevention. The environmental variables were used in this research including five climatic variables (maximum temperature, average temperature, precipitation, solar radiation, and wind speed) and six topographic variables (vegetation types, elevation, slope, aspect, topographic wetness index, and distances from road). These variables were represented as raster layers, stratified into ranked classes before being weighted overlaid to calculate the total points. Forest fire risks were classified into five levels from very low to very high based on the calculation results. The final result showed that 16% area in the very high-risk zone, 24% area in the high-risk region, 49% area in the medium and low-risk zone, and 11% area appeared with the lowest fire risk. Very high-risk areas are distributed at low elevations along the southwest boundary of the natural park. The forest fire risk map in Tam Dao National Park will be a useful reference source for forest management and protection in the fire season.